2018
DOI: 10.1017/jsi.2018.2
|View full text |Cite
|
Sign up to set email alerts
|

(Re)-Defining ‘Teacher’: Preservice Teachers with Disabilities in Canadian Teacher Education Programs

Abstract: Directors of Student Teaching from the Western Canadian provinces participated in focus groups about the realities and decision-making processes around practicum for preservice teachers with disabilities. Results showed current standards, when applied rigidly, served to reify a static, homogenous, and unrealistic definition of ‘teacher’ that marginalises preservice teachers with disabilities. However, the effort of directors to challenge this notion of ‘teacher’, framed within the constructionist model of disa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
4
0
1
Order By: Relevance
“…Such comparisons would have provided a means to interpret the evidence from Thailand. For example, a Canadian study (see Kitchenham & Chasteauneuf, 2010) identified shortages of specialist teachers in science, mathematics and special education in remote and rural areas with ìfew incentives for teachers to go to those areas.î Another Canadian study found that pre-service teachers with disabilities were marginalised in their programs (see Wilson, Sokal, & Woloshyn, 2018). A study in Ontario, Canada revealed that although there was recognition of the need for diversity in teacher education, ìvarious groups ñ including first-generation students, students with disabilities, students of Aboriginal descent, and other racialized minorities ñ are underrepresented in Ontarioís colleges and universitiesî (Holden & Kitchen, 2018, p. 45).…”
Section: Resultsmentioning
confidence: 99%
“…Such comparisons would have provided a means to interpret the evidence from Thailand. For example, a Canadian study (see Kitchenham & Chasteauneuf, 2010) identified shortages of specialist teachers in science, mathematics and special education in remote and rural areas with ìfew incentives for teachers to go to those areas.î Another Canadian study found that pre-service teachers with disabilities were marginalised in their programs (see Wilson, Sokal, & Woloshyn, 2018). A study in Ontario, Canada revealed that although there was recognition of the need for diversity in teacher education, ìvarious groups ñ including first-generation students, students with disabilities, students of Aboriginal descent, and other racialized minorities ñ are underrepresented in Ontarioís colleges and universitiesî (Holden & Kitchen, 2018, p. 45).…”
Section: Resultsmentioning
confidence: 99%
“…Gli insegnanti con disabilità/DSA, infatti, spesso si sono sentiti confinati come outsider sul posto di lavoro (Makris, 2018). Nascondere la propria disabilità/DSA, tuttavia, richiede un grande sforzo e può significare rinunciare agli accomodamenti ragionevoli (e, di conseguenza, ripercuotersi sulle possibilità di una piena inclusione nella professione) o causare isolamento sociale (Wilson, Sokal, & Woloshyn, 2018). Paradossalmente, la decisione sulla rivelazione delle proprie difficoltà appare, nei nostri studi, meno complessa nei confronti degli studenti, forse in virtù del fatto che i docenti sembrano attingere alle proprie esperienze personali per apportare cambiamenti inclusivi alla prassi didattica (Dvir, 2015;Moore et al, 2020).…”
Section: Discussioneunclassified
“…The current project is a re-examination of a synthesis of findings of our previous studies (Sokal et al, 2017;Wilson et al, 2018). Our intent is not to re-iterate our previous collection of findings, but rather to examine how the processes and decision-making of DSTs reflect their adoption of the tenets of specific theories of disability and conceptions of teacher.…”
Section: Description Of the Data Setsmentioning
confidence: 99%
“…The first reported on an anonymous survey of ten DSTs from Ontario, Manitoba, Saskatchewan, Alberta, and British Columbia (Sokal et al, 2017), with two participants from each province. The second study (Wilson et al, 2018) reported on two follow-up focus groups of 1.5 hours each involving 14 DSTs from four Western Canadian provinces (2 from Manitoba, 4 from Alberta, 6 from British Columbia, and 2 from Saskatchewan), allowing more in-depth analysis and understanding of the survey results. Given that the surveys were anonymous, it is possible that some participants took part in both studies.…”
Section: Description Of the Data Setsmentioning
confidence: 99%
See 1 more Smart Citation